“Tel Père, Tel Fils !”: The Franciscans on Racial Degeneration, Heredity, and Eugenics (1906-1954) - Auffrey, Vincent (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2025)
Between 1906 and 1954, the Franciscan order was at the helm of two important social movements in Québec: the temperance and Catholic family movements. In their journals La Tempérance (1906–1937) and La Famille (1937–1954), Franciscan writers invoked the hereditary consequences of alcoholism for future generations and the looming threat of racial degeneration. This paper examines how local religious and scientific elites contributed to the growing acceptance and dissemination of eugenics in early-twentieth century Québec. It focuses on the Franciscans’ writing about heredity, degeneration, and eugenics, and especially on Hervé Blais’s 1942 publication Les tendances eugénistes au Canada.